SUBSTANTINATION OF VACINE-PROPHILACSIS AGAINST INFLUENZA IN CHILDREN OF EARLY AGE - A. P. Cherdantsev (Детские инфекции (Москва))
Influenza is one of the most dangerous infection for children of early age. Vaccine-prophylactics against influenza is the most important way to confine the spreading of the infection and to localize epidemic outbreak among children. Modern vaccines have a high level of safety and efficacy. It allows to apply them during the first year of life. The WHO and ECDC point out the necessity of group and individual immunity development among children of different age groups. The authors demonstrated important role of immunization against influenza for the mother to enhance resistance to the infection in the child in the first months of its life.